Poly[[bis[mu(2)-N,N `-bis(2-pyridylmethyl)-oxalamide-kappa N-4,O:N `,O `][mu(2)-N,' N-bis(2-pyridylmethyl)oxalamide-kappa N-2:N `]disilver(I)] bis(trifluoromethanesulfonate)] - Arman, H.D.; Miller, T.; Poplaukhin, P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title salt, [Ag(C14H14N4O2)(1.5)]-(CF3SO3), comprises a Ag+ cation, three half-molecules of N,N'-bis(2-pyridylmethyl)oxalamide (each of which is disposed about a centre of inversion) and a trifluoromethanesulfonate anion. Distinct coordination modes are found for the bridging ligands, i.e., a mu(2),kappa(2) -bridging mode involving pyridine N atoms for one ligand, and a mu(2),kappa(4)-bridging mode, employing both pyridine N and amide O atoms for the remaining ligands. The Ag+ cations, which are in a distorted square-pyramidal coordination, and the ligands combine to form a two-dimensional array parallel to (101); these arrays are connected into a three-dimensional structure by trifluoromethanesulfonate anions via N-H center dot center dot center dot O, C-H center dot center dot center dot O, and C-F center dot center dot center dot O interactions.